This is how India reacted to lockdown during COVID-19 pandemic: an online survey - Upreti, Gaurav; Upreti, Ishwar Chandra; Lohani, Puran Chandra (International Journal Of Community Medicine And Public Health, 2021)
Background: During the COVID-19 pandemic, the lockdown was used as a public health measure throughout the world including India to reduce transmission of the disease. Not only did the lockdown significantly decrease the growth rate of the COVID-19 pandemic, but also immediately and drastically changed patterns of daily life and behavior of people across India. Methods: This online survey was conducted during phases 2 and 3 of lockdown to study the effect of lockdown on the daily routine of people, find out its psychological impact and study the factors contributing to it. Results: During the lockdown, 75.2% of respondents were working from home with 36.8% reporting a decrease in the number of working hours. There was a significant increase in the mean duration of sleep, exercise/meditation, and time spent with family, on social media/OTT platforms during the lockdown. The lockdown resulted in widespread compliance with public health directives. There was a wide spectrum of symptoms of psychological distress among the study subjects the commonest being anxiety (70%) followed by fear of infection (about 35%). Female gender, extrovert personality, married status, having children, lower socioeconomic status, fear of infection, loneliness, inadequate basic supplies, a longer period of lockdown, and inadequate information were found to be associated with negative psychological impact. Conclusions: Lockdown brought significant changes in the daily routine and behaviour of people with a wide spectrum of negative psychological impacts. Effective measures should be taken to mitigate its effect as a part of the quarantine planning process.